Numerical Simulation Study on Effect of Freezing Temperature on Quality of Fresh Frozen Plasma - Jia Chunxiao; Liu Baolin (Zhileng xuebao)
When the central temperature of the plasma bag reaches ?30 ℃ the freezing process is finished. The cooling rate and the temperature uniformity of the plasma bag during freezing are two key factors for determining the freezing quality of plasma. In this study, the thermophysical parameters of plasma were measured experimentally. The effects of different freezing temperatures on the cooling rate and temperature uniformity of the plasma bag were investigated through numerical simulation. The results show that a lower freezing temperature can shorten the time to reach ?30 ℃, but the temperature uniformity of the plasma bag becomes worse. At different freezing temperatures, the maximum temperature of plasma is at the place where there is a gap between the plasma bag and the freezing plate, due to the relatively poor heat transfer capability of air. In summary, increasing the contact area between the inner wall of the freezer and plasma bag or increasing the air flow velocity and turbulence intensity can significantly increase the cooling rate and temperature uniformity of the plasma.